Konsep Kewarganegaraan dalam Pemikiran Tokoh Tokoh Politik Terkemuka - Zira Zulvi Anjani; Nabila Safitri; Afriani Afriani; Iyang Ragel Harnesti; Nadya Hafizah; Siti kholizah Nasution (Institute of Advanced Knowledge and Science, 2024)
This study investigates in depth the concept of citizenship in the thoughts of prominent political figures such as Aristotle, Cicero, Locke, Rousseau, Arendt, and Marshall using a qualitative approach through a literature review. The main objective of this study is to investigate the evolution of the concept of citizenship from a philosophical and theoretical perspective. This study shows that citizenship does not only focus on formal legal rights, but also considers the importance of active participation of individuals in political life and the protection of human rights. The results of the analysis indicate that these concepts play a key role in shaping the structure of modern democratic and pluralistic societies, especially in facing increasingly complex and diverse global challenges.